Triplex sonographic evaluation of portal vein indices among adults in Port Harcourt, Nigeria - Gbenga Jacob Aderibigbe; Chukwuemeka Agi; Ebbi Donald Robinson (Journal of Medical Ultrasound, 2022)
Background: Chronic liver disease is characterized by progressive hepatic fibrosis and changes in hepatic vascular hemodynamics. Sonography is a readily available tool in the assessment of the hepatic hemodynamic alterations that occur in chronic liver diseases. Aim: This study was aimed at sonographically determining the portal vein indices in apparently healthy adults by estimating the portal vein diameter, cross-sectional area, and portal vein velocity. Methods: This was a prospective, cross-sectional study carried out among 62 apparently healthy individuals. The participants underwent gray scale and Doppler ultrasonographic examinations of the portal vein. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) IBM Corp. version 23.0 (Armonk, NY: USA). The comparison of means of two groups was with the unpaired t-test, and level of significance was set at 5% (P < 0.05). Results: Forty-six (74.2%) of the 62 participants recruited were male and 16 (25.8%) were female. Participants were aged 18–65 years with a mean age of 39.90 ± 10.34 years. The means of portal vein diameter, cross-sectional area, and portal vein velocity are 1.15 ± 0.12 cm, 0.88 ± 0.18 cm2, and 18.37 ± 2.04 cm/s, respectively. There was no statistically significant difference of all portal vein ultrasound parameters between males and females, except portal vein flow velocity which was higher in males, t-test = 2.273 and P = 0.027 (>0.05). There was no significant correlation between age and ultrasound parameters P > 0.05. Conclusion: The normal values of portal vein diameter, cross-sectional area, and portal vein velocity were established.